2007
DOI: 10.1093/jb/mvm150
|View full text |Cite
|
Sign up to set email alerts
|

Na+- and K+-Dependent Oligomeric Interconversion among   -Protomers, Diprotomers and Higher Oligomers in Solubilized Na+/K+-ATPase

Abstract: Protein fractions of a higher-oligomer (H), (alphabeta)(2)-diprotomer (D) and alphabeta-protomer (P) were separated from dog kidney Na(+)/K(+)-ATPase solubilized in the presence of NaCl and KCl. Na(+)/K(+)-dependent interconversion of the oligomers was analysed using HPLC at 0 degrees C. With increasing KCl concentrations, the content or amount of D increased from 27.6 to 54.3% of total protein, i.e. DeltaC(max) = 26.7%. DeltaC(max) for the sum of D and H was equivalent to the absolute value of DeltaC(max) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 63 publications
5
36
0
1
Order By: Relevance
“…Natural phosphatidylserine (PS) purified from ox brain and four kinds of synthetic PS with various lengths of acyl chains, such as dioleoyl (C18:1), dipalmytoyl (C16:0), dimyristoyl (C14:0), and dioctanoyl (C8:0), were purchased from Avanti Polar Lipids, Inc. (Alabaster, AL). Other chemicals used have been described previously (10). Special care was taken to minimize contamination by Na + and K + (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural phosphatidylserine (PS) purified from ox brain and four kinds of synthetic PS with various lengths of acyl chains, such as dioleoyl (C18:1), dipalmytoyl (C16:0), dimyristoyl (C14:0), and dioctanoyl (C8:0), were purchased from Avanti Polar Lipids, Inc. (Alabaster, AL). Other chemicals used have been described previously (10). Special care was taken to minimize contamination by Na + and K + (10).…”
Section: Methodsmentioning
confidence: 99%
“…Other chemicals used have been described previously (10). Special care was taken to minimize contamination by Na + and K + (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, indeed, it was established that sarcoplasmic reticulum Ca 2ϩ -ATPase, solubilized as a monomer by C 12 E 8 , retains all of the basic features required to function as a Ca 2ϩ -transporting unit, regardless of the tendency of this Ca 2ϩ pump to undergo reversible and irreversible self-association (20). For Na ϩ ,K ϩ -ATPase, this also appears to be the case (28 -30), although dimerization of the ␣,␤-protomer is a more pronounced feature of this ATPase than it is for Ca 2ϩ -ATPase (27,(31)(32)(33). Application of the same surfactant strategy to H ϩ ,K ϩ -ATPase is fraught with the problem that it is difficult to avoid either irreversible or reversible inhibition of enzyme activity in the detergent-solubilized state.…”
Section: Surfactant Solubilization Of Tubular Vesicular Membranes Andmentioning
confidence: 97%
“…Despite the probable presence of protein-protein interactions in the native membrane, which may affect enzyme activity (25,26), they all indicate monomeric Ca 2ϩ -ATPase as the fundamental Ca 2ϩ -transporting unit. For Na ϩ ,K ϩ -ATPase, the evidence is more equivocal in that both monomeric and dimeric forms with retention of enzyme activity have been detected by analytical ultracentrifugation (27)(28)(29)(30) and by HPLC (31)(32)(33). The requirement of an oligomeric structure as a sine qua non to preserve transport and enzyme activity, as claimed for H ϩ ,K ϩ -ATPase and reported in a recent review (34), is not indicated by either the detergent data or by the available threedimensional x-ray diffraction structures of Ca 2ϩ -ATPase (35,36), Na ϩ ,K ϩ -ATPase (37)(38)(39), and H ϩ -ATPase (40,41).…”
mentioning
confidence: 99%